Plugging and Its Stability Evaluation for the Ore Pass in the Nonempty Condition Based on Controllable Grouting of Cement-Sodium Silicate Grout - Ye Yuan; Dengpan Qiao; Shibo Yu (Geofluids)
Aimed at the problem to plug the main ore pass with the large collapse at Xingshan Iron Mine, the viscosity-time test and the heap perfusion test of cement-silicate grout in a loose rock mass are carried out. The relationship between the vertical diffusion distance of cement-silicate grout and setting time of grout is studied, and research results are applied to the design of plugging engineering of the main ore pass in -330 m. Based on the numerical simulation of the plugging structure and the long-term stress monitoring of the cable sensors, the stability of the plugging structure itself and the control for the movement of shafts nearby are comprehensively evaluated. The test results show that for a specific loose rock mass, the vertical diffusion distance of cement-silicate grout in the loose rock mass is a power function of grout setting time. Based on the design concept to plug the main ore pass with the large collapse using artificially constructed “bite-bonded arch,” the plugging design and construction procedures are proposed. A numerical model and long-term monitoring of cable stress show that the plugging structure is stable and has an obvious effect on the control movement of abutment shafts.